Geometric and computational spectral theory : Seminaire de Mathematiques Superieures, June 15-26, 2015, Centre de Recherches Mathematiques, Université de Montréal, Montréal, Québec, Canada - Girouard, Alexandre, 1976- (Contemporary mathematics (American Mathematical Society), 2017)
The book is a collection of lecture notes and survey papers based on the mini-courses given by leading experts at the 2015 Séminaire de Mathématiques Supérieures on Geometric and Computational Spectral Theory, held from June 15-26, 2015, at the Centre de Recherches Mathématiques, Université de Montréal, Montréal, Quebec, Canada.